Morphology and ecology of Sibon snakes (Squamata: Dipsadidae) from two forests in Central America - Todd R. Lewis; Rowland K. Griffin; Paul B. C. Grant; Alex Figueroa; Julie M. Ray; Kirsty E. Graham; Gabriel David (Phyllomedusa: Journal of Herpetology, 2013)
abundance, behavior, body conditionPhysical measurements, abundance, and ecological observations were recorded for Sibon annulatus, S. argus, S. longifrenis, and S. nebulatus at two Neotropical habitats: a lowland swamp forest in Costa Rica and a montane cloud forest in Panama. Fourty-four and 58 adult snakes were recorded from Costa Rica and Panama, respectively. Differences in morphology and body condition showed minimal significant differences among species from both geographical locations. Observations of feeding, reproduction, abundance, distribution, and a new size record for S. annulatus are discussed.